Expert System For Diagnosing Hemophilia In Children Using Case Based Reasoning - Subrianto Chandra; Sumijan Sumijan; Eka Praja Wiyata Mandala (Indonesian Journal of Artificial Intelligence and Data Mining, 2019)
Many people who have children do not know about hemophilia, because this disease is one of the rare diseases. Hemophilia is a genetic disorder in the blood caused by a lack of blood clotting factors. Therefore there is a need for information for the public to be able to find out about this disease, so that when there is an unnatural bleeding, early treatment can be done properly.Therefore an expert system was designed to diagnose early hemophilia in children.The method used in this expert system is the Case Based Reasoning method. The Case Based Reasoning method is a method used to solve a new case by adapting the symptoms found in previous cases that are similar to the new case.This expert system can provide solutions / early prevention of the diagnostic process carried out. Expert system applications are designed based on websites using the PHP programming language.